Tyrosol and Hydroxytyrosol Two Main Components of Olive Oil, Protect N2a Cells Against Amyloid-β-Induced Toxicity. Involvement of the NF-κB Signaling - St-Laurent-Thibault, C.; Arseneault, M.; Longpre, F.; Ramassamy, C. (Current Alzheimer Research, 2011)
Alzheimer's disease (AD) is the most common form of dementia. Recently, a number of epidemiological studies have shown that some dietary factors such as low antioxidants and vitamins intake could increase the risk of AD. In the opposite, diets rich in unsaturated fatty acids, in polyphenols, vitamins and antioxidants were identified as preventive factors. Several studies have reported that adherence to the Mediterranean diet (MeDi) was associated with a reduction in incidence of dementia. The beneficial effect of MeDi may be the result of the association of some individual and nonidentified food components and high consumption of olive oil. In this study we have investigated the protective effects of two components of olive oil, tyrosol (Tyr) and hydroxytyrosol (OH-Tyr), against Aβ-induced toxicity. In cultured neuroblastoma N2a cells, we found that Aβ25-35 (100 μg/ml) treatment induced a decrease of glutathione (GSH), and the activation of the transcription factor NF-κB and cell death. Our results demonstrated that the number of cell death decreased when cells were co-treated with Aβ and Tyr or OH-Tyr. However, neither of these phenolic compounds was able to prevent the decrease of GSH induced by H2O2 or Aβ. We found that the increase in the nuclear translocation of the NF-κB subunits after Aβ exposure was attenuated in the presence of Tyr or OH-Tyr. These results identified two individual food components of the MeDi as neuroprotective agent against Aβ and their potential involvement in the beneficial effect of the MeDi for the prevention of AD.
Keywords: Alzheimer' s disease